Clique number and Girth of the Rough Co-zero Divisor Graph - et. al., Dr.B. Praba, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to determine the Clique number, Girth and Maximal independence number of the Rough Co-zero divisor Graph corresponding to a Rough semiring (T, ∆, ∇). The methodology of these graph theoretical parameters are obtained using partition graph of Rough co-zero divisor graph . Though the number of vertices in is , , the partition graph plays a significant role in determining the results the Clique number of as and the Girth is 3 and Maximal independence number of is . All these concepts are illustrated with suitable examples. AMS Classification 05C69, 05B10, 05C07, 05A18.